Faktor Determinan dalam Kepatuhan Penggunaan APD Tenaga Keperawatan Gigi Rumah Sakit selama Pandemi - Laily Maghfira Noor Ridarsyah; Ayun Sriatmi; Henry Setyawan Susanto (Jurnal Manajemen Kesehatan Indonesia, 2022)
Hospitals are complex, expert and capital intensive health care institutions. During the Covid-19 pandemic, many cases of health workers infected with Covid-19 were described by data on the death rates of health workers in various countries. The use of Personal Protective Equipment (PPE) for nurses is very influential because it can prevent exposure to infectious diseases. the risk of contracting the disease in nurses will increase.The purpose of this study was to analyze factors related to compliance with the use of PPE for dental workers in hospitals during the pandemic.This is a quantitative research with a cross-sectional approach. The target population in this study were all 65 medical personnel at RSIGM Sultan Agung Semarang. The sampling technique used in the study was the total population.The results showed that the information provided, leadership and perceived benefits will have a positive effect on dentist compliance in the use of PPE, while imbalance, and the environment have no positive effect on dentist compliance in the use of  PPE. Information provided, imbalance, leadership, environment and perceived benefits together have a relationship with dentist compliance in using personal protective equipment.Doctors and dental nurses need to maintain their mindset that they will feel happy if the patient and himself are protected from the Covid-19 virus. It is necessary to know that the use of PPE does not hamper the services provided because PPE is only an additional tool for personal and patient protection against the Covid-19 virus.